Pendampingan HKI Karya Invensi Guru dan Siswa di SMK Lemuria Kudus - Zainul Arifin; Miftah Arifin; Purwo Adi Wibowo (Journal of Dedicators Community, 2019)
UNISNU Community Service Activities Based on Fostered Schools aims to provide assistance, development of work and determination of work to identify inventions of the work of teachers and students at the Kudus Lemuria Vocational School of Furniture Engineering to submit a Intellectual Property Rights request of their invention. The output of this activity are : 1) increasing the effectiveness and innovation of teachers & students to work inventions; 2) increasing partner understanding of the work of invention 3) increasing the teacher's ability in making inventions. The program was carried out by the UNISNU HKI Center with the methods are socialization and assistance in registering the work of teacher and student inventions. Activity stages are: 1) Preparation Phase; 2) Assessment Phase; 3) Planning or Alternative Program Planning Phase; 4) Action Plan Phase; 5) Program or Activity Implementation Phase; 6) Evaluation Phase. The results of this service are: 1) awareness of the importance of copyright protection in the work produced, 2) identified works owned 3) willingness to submit legal protection to the works produced and Copyright certificates from the Director General of Intellectual Property Ministry of Law and Human Right.